Near-surface viscosity and complex crystal growth behavior in Se90Te10 thin films and bulk surface - Martinková, Simona; Včeláková, Michaela; Vaculík, David; Pilný, Petr; Kurka, Michal; Barták, Jaroslav (Elsevier Science SA, 2024)
Considering the resurgence of interest in selenium and tellurium -based solar cells and the inter alia related relationship between the device efficiency and post -growth annealing for crystallization, increased attention should be given to the understanding of crystallization process (formation of crystals, crystal positions, and nucleation and crystal growth kinetics). This work summarizes an extensive study of the crystal growth rates and near -surface viscosity at the Se90Te10 bulk surface and in thin films using nanoindentation and measurements of thermal grating decay. The crystal growth in Se90Te10 thin films occurs at two positions - at the thin filmsubstrate interface and the free surface of the thin film. Here, the crystallization of the interface crystals was quantitatively studied using microscopy down to the Tg and below. The influence of different substrates, illumination, and aging on crystal growth rates was tested in the studied thin films to understand the crystal growth properly. Regarding the crystal growth at the bulk surface, the sample size -dependent crystal growth rates were found. The values can be found in the region limited by growth rates of volume crystals (lower limit) and those found in thin films (upper limit). The growth data are combined with the near -surface viscosities measured in bulk samples and thin films to assess a suitable growth model for the description and prediction of the growth data in a wide temperature range.
Viskozita a krystalový růst v Se90Te10 tenkých filmech a na povrchu objemového skla
Keywords: Thin films; Crystal growth; Near -surface viscosity; Microscopy; Nanoindentation; Viskozita; růst krystalů; Se90Te10; film; povrchu; skla